On the Integration of In Silico Drug Design Methods for Drug Repurposing - March-Vila, Eric; Pinzi, Luca; Sturm, Noé; Tinivella, Annachiara; Engkvist, Ola; Chen, Hongming; Rastelli, Giulio (Frontiers in Pharmacology, 2017)
Drug repurposing has become an important branch of drug discovery. Several computational approaches that help to uncover new repurposing opportunities and aid the discovery process have been put forward, or adapted from previous applications. A number of successful exam-ples are now available. Overall, future developments will greatly benefit from integration of different methods, approaches and disciplines. Steps forward in this direction are expected to help to clarify, and therefore to rationally predict, new drug-target, target-disease, and ulti-mately drug-disease associations.